Revised Short Screening Version of the Profile of Mood States (POMS) From the German General Population - Petrowski, Katja; Albani, Cornelia; Zenger, Markus; Brähler, Elmar; Schmalbach, Bjarne (Frontiers in Psychology, 2021)
The present study was conducted with the aim of constructing and validating a short form of the Profile of Mood States (POMS). The POMS is a widely-applied measure for the assessment of an individual’s mood. Thus, it is of great relevance for many research questions in clinical and social psychology. To develop the short scale, we first examined psychometric properties and found the optimal 16-item solution among all valid combinations of the full POMS in an exploratory subsample (n = 1,029) of our complete representative sample of the German general population. We then validated this model in a confirmatory subsample (n = 977). Additionally, we examined its invariance across age groups and sex, as well as its reliability. Our results indicate that the POMS-16 is a valid and reliable measure of mood states with minimal losses compared to the 35-item version. Particularly where brevity and an economical assessment is desired, the POMS-16 should be considered.